2013
DOI: 10.1007/s11136-013-0389-6
|View full text |Cite
|
Sign up to set email alerts
|

Increases in physical activity may affect quality of life differently in men and women: the PACE project

Abstract: Purpose Obesity is associated with impaired quality of life (QoL), but less is known about physical activity. We investigated how decreases in body mass index (BMI) and increases in activity affect obesity-specific QoL and potential gender differences in associations. Methods In a large worksite-randomized trial of a multilevel intervention on diet and physical activity behaviors, we conducted a cohort analysis at two years of follow-up. Self-reported activity and Obesity and Weight-Loss Quality Of Life (OWL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 26 publications
2
21
1
4
Order By: Relevance
“…In contrast, a randomized controlled clinical trial of inactive persons [16] with a program to promote physical activity as an intervention, found no statistically significant changes between the experimental and control group in regard to the quality of life related to health. Other authors have evaluated the quality of life with specific tools for their study population (elderly, obese and patients with cystic fibrosis) [22, 45, 46]. Similar to our work, they found that physical activity is directly associated with quality of life.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, a randomized controlled clinical trial of inactive persons [16] with a program to promote physical activity as an intervention, found no statistically significant changes between the experimental and control group in regard to the quality of life related to health. Other authors have evaluated the quality of life with specific tools for their study population (elderly, obese and patients with cystic fibrosis) [22, 45, 46]. Similar to our work, they found that physical activity is directly associated with quality of life.…”
Section: Discussionsupporting
confidence: 86%
“…Our study results suggested that the efficacy of this intervention strategy varied between boys and girls, with a much clearer effect in boys, which is inconsistent with the results of previous studies [40,41]. Brown DW et al [42] have previously found that physical activity improved quality of life for both men and women.…”
Section: Discussioncontrasting
confidence: 99%
“…Smoking is a risk factor that tends to present with other factors, such as alcohol consumption and physical inactivity [ 54 , 55 ], which is partly consistent with our results. Low levels of physical activity were in fact found to be associated to reduced QoL in a large number of studies [ 56 , 57 ], as well as to obesity or overweight [ 58 , 59 ]. In contrast with these results, our data did not support the association between obesity, increased WC and QoL, despite a more than half of our sample was obese or overweight and one-third had high-risk WC.…”
Section: Discussionmentioning
confidence: 99%